PROSPEK BRIKET BATUBARA LIGNIT SEBAGAI BAHAN BAKAR ALTERNATIF SEKTOR RUMAH TANGGA DAN INDUSTRI KECIL - Soedjoko Tirtosoekotjo; Bambang Suwondo Rahardjo (Badan Pengkajian dan Penerapan Teknologi, 2009)
Market coal briquette compartment in Indonesia is estimated still big enough,considering kerosene and firewood which was usually used as small industrialand rural household sector fuel progressively scarce and costly if withoutsubsidy. Coal briquette of lignit made of low rank coal without carbonizationprocess and without binder, so that can become alternative fuel which iscompetitif, safe, efficient and environmental friendliness. Volatile matter contentcan be decreased by using special design of stove to burn it by fire tongue on thesurface of stove to yield completely combustion. Continueing usage of coalbriquette as alternative fuel substitution of kerosene and or firewood especially inrural, can be conducted by given system and sustanable supply guarantee,quality improvement, economical charcoal burner device of the environmentalfriendly, efficiently and routine promotion activities.Kata kunci: briket lignit, bahan bakar alternatif, rumah tangga & industri kecil